Diffused Larengeal Tuberculosis Case Report - Gök, Üzeyir; Keleş, Erol (Fırat University, 2001)
Tuberculosis is still an important health problem in our country as well as in the world. Larynx tuberculosis is rarely seen from of extrapulmoner tuberculosis. Laryngeal tuberculosis should be considered in diagnosis when patients with history of long term alcohol and applied with tobacco use complaints of hoarseness which is unresponsive to treatment. Unsuitable social environmet and nutritional habits may contribute on development of laryngeal tuberculosis. Laryngeal tuberculosis may be confused with malignant laryngeal tumors in elder patients in terms of lesions appearence and clinical features. In present article a 33 years old male patient with laryngeal tuberculosis demonstrating hoarseness for 4 months, diffused laryngeal occupation as diagnosed by indirect laryngoscopy was presented along with literature knowledge.

Tüberküloz halen ülkemizde ve dünyada önemli bir sağlık sorunu olarak devam etmektedir. Larenks tüberkülozu nadir görülen akciğer dışı organ tüberkülozlarından biridir. Uygunsuz sosyal koşullar, uzun süreli sigara ve alkol kullanımı öyküsü olan ve tedaviye cevap vermeyen ses kısıklığı şikayetleri ile başvuran hastada, nadir görülmesine rağmen larengeal tüberküloz tanıda düşünülmelidir. Larengeal tüberküloz yaşlı hastalarda gerek larengeal lezyonun görünümü gerekse klinik seyir açısından sıklıkla malignensi ile karışabilir. Bu makalede, 33 yaşında yaklaşık 4 aydır ses kısıklığı, indirekt larengoskopide yaygın larengeal tutulumu olan, larengeal tüberkülozlu erkek hasta literatür bilgisi ile sunuldu.
YAYGIN LARENGEAL TÜBERKÜLOZ VAKA TAKDİMİ